2018
DOI: 10.1108/imds-06-2017-0256
|View full text |Cite
|
Sign up to set email alerts
|

Promoting radical innovation through end-user computing satisfaction

Abstract: Purpose The purpose of this paper is to provide empirical evidence of the relationship between end-user computing satisfaction (EUCS) and radical innovation, using organizational learning as an explanatory variable. Design/methodology/approach An empirical study was conducted in a population of 402 Spanish companies. A sample of 251 valid questionnaires was obtained. Structural equations were used to validate the proposed hypotheses. Findings Organizational learning capability fully mediates the relationsh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0
1

Year Published

2019
2019
2025
2025

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 75 publications
1
11
0
1
Order By: Relevance
“…Moreover, it is apparent that marketing and sales managers do not always keep up with their digitally empowered customers (Day, 2011). However, the use of IT tools and the flexibilities in IT infrastructures are factors contributing to customer interactions and business success in terms of creating and capturing value by managers (Drnevich and Croson, 2013; Benitez et al , 2018; Domínguez-Escrig et al , 2018). Furthermore, IT is observed to not only advance marketing tools but also marketing methods by creating new enabling technologies.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, it is apparent that marketing and sales managers do not always keep up with their digitally empowered customers (Day, 2011). However, the use of IT tools and the flexibilities in IT infrastructures are factors contributing to customer interactions and business success in terms of creating and capturing value by managers (Drnevich and Croson, 2013; Benitez et al , 2018; Domínguez-Escrig et al , 2018). Furthermore, IT is observed to not only advance marketing tools but also marketing methods by creating new enabling technologies.…”
Section: Introductionmentioning
confidence: 99%
“…Intensified competition, opportunities and changing customer purchasing behavior (Ianenko et al , 2019) have increased the need for academic attention. Recently, researchers have shown a growing interest in the alignment of the IT function (Ricciardi et al , 2017; Domínguez-Escrig et al , 2018) and its strategy (Coltman et al , 2015; Gerow et al , 2014; Bharadwaj et al , 2013) within the organization but have rarely focused on marketing functions. Some scholars underline the demand for a more innovative marketing department (Verhoef and Leeflang, 2010) and reduced innovation barriers (Maldonado-Guzmán et al , 2017); also, there is ample research about the relationship between marketing and other major functions besides IT (Dewsnap and Jobber, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…The present research is part of the trend of studies that disentangle the antecedents of innovation within organizations. Precedent research found evidence of different facilitators for innovation to occur, such as appropriate information systems (Domínguez-Escrig et al , 2018), leadership style (Oke et al , 2009) or organizational learning (Jimenez-Jimenez et al , 2008), to name but a few. Among the enablers of innovation within companies, leadership plays an essential role (Prasad and Junni, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…As a response to this situation, Yukl (2012) suggested to study how specific leader behaviors affect different outcomes. This approach has been followed to study the effect of leaders’ behaviors on innovation (Domínguez-Escrig et al , 2018; Mallén et al , 2015). Therefore, the present research follows this trend and analyzes the influence of leaders’ humility on innovation.…”
Section: Introductionmentioning
confidence: 99%
“…Each element has questions that will be asked to the user. [7], [8]. The sample questions for this study can be seen in Table 1.…”
Section: End-user Computing Satisfactionmentioning
confidence: 99%